Recognition and Utilization of Foreign Qualifications and Skills in the Canadian Labor Market - Annen, Silvia [Verfasser] (My University, 2018)
"Canadian society is characterized by a plurality of immigrants. Canadian migration policy and corresponding recognition approaches are strongly geared to economic criteria as well as qualifications and skills. This paper addresses the question of how immigrants to Canada use their foreign qualifications and skills in their current jobs. Qualification and skill mismatch are aspects of deficient integration of immigrants in the labor market. PIAAC data was used to investigate to what extent immigrants are affected by those phenomena and if there are significant differences between natives and immigrants or among different immigrant subgroups. The immigrant subgroups were categorized using the regions where the highest qualifications were acquired, and the migration programs were considered. The results show that immigrants are more often affected by the problem of over-qualification, while native Canadians are more often under-qualified. In contrast, skill mismatch occurs to a smaller extent among immigrants and native Canadians; the problem mainly appears among immigrants being under-skilled. A regression model confirms the negative influence of qualification and skill mismatch on employees' wages." (author's abstract; BIBB-Doku)
Keywords: P 1.5 Migranten; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; G 1.2.3.1 Potenziale; I 2.3.2 Nordamerika; Einwanderer; Auslandsqualifikation; Anerkennung; Qualifikationsverwertung; Arbeitsmarkt; Überqualifikation; Kanada